Elastic Properties of Compressed Sitka Spruce Reinforced with Biodegradable Poly (vinyl alcohol) - UEHARA, Tohru; YOSHIHARA, Hiroshi; TAKADA, Hiroyuki (Nihon Kikai Gakkai ronbunshū. A, 2008)
A composite material was produced by compression treatment of Sitka spruce plate soaked into biodegradable poly (vinyl alcohol) under various treatment conditions. To enhance the wettability of specimen, corona discharge and cutting of holes were conducted as pre-treatments. The pre-treated specimen was soaked into the poly (vinyl alcohol), then it was compressed and fixed in a airtight atmosphere. For examining the influence of the treatments on the elastic properties of composite material, Young's modulus in the longitudinal direction and Poisson's ratios and shear moduli in the longitudinal-radial and longitudinal-tangential planes of the composite material were measured. The test results indicated that these elastic properties can be improved when the composite material is fabricated under the appropriate pre-treatment conditions.